THE EFFECTIVENESS OF USING CLUSTERING TECHNIQUE TOWARD WRITING PROCEDURE TEXT - Risma Rahajeng Lestari; Neny Triana Dewi (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2022)
This research was conducted to measure the effectiveness of cluster techniques in writing text procedures from students as students of Roudlotun Nasyiin Mojokerto. The researcher uses quasi experimental research for design. This design involves two classes as research subjects, the experimental class and the control class. These classes have similar abilities in English achievement. The researcher gave experimental treatment in treatment class and the researcher gave control treatment in control class. After doing the treatments in each class, the researcher gave post-test. The post-test scores in each class will be compared to measure the impact of doing these treatments. There are two variables in this research, independent variable and dependent variable. Independent variable is clustering technique and dependent variable is writing achievement. This treatment is given during some meeting before taking the data. The research result students’ ability in writing after taught by using clustering technique was very good. In short, clustering technique was an appropriate strategy to write a text, especially procedure text. The writing students’ ability taught by using non- clustering technique was lower than the students were taught by using clustering technique. The result of t-test was 7,153. After got the score, the researcher compared it with t- table (df = n1 + n2 – 2 = 72 ; significance 5% = 0.05). The value of t-table was 1.666. It signed that Ha was accepted and H0 was refused.